Reciprocal teaching applied in Hybrid-Based DaF (Deutsch als Fremdsprache) learning - Aini, Desti Nur; Caesaria, Antika Cahaya (Hong Kong Journal of Social Sciences, 2022)
The purpose of this study is to describe the process of application and implications of the hybrid learning-based reciprocal teaching method focusing on reading skills of German texts at the A1 level in accordance with the European standard frame of reference (Gemeinsamer Europäischer Referenzrahmen - GER) and it was implemented in a hybrid learning. This was undertaken to ensure effective learning by mixing up the online and face-to-face methods. The reciprocal teaching method is implemented through four stages of understanding, namely asking questions, predicting, clarifying, and summarizing. A qualitative descriptive method is used to describe the phenomenon of learning based on hybrid learning. The source of data in this study were 36 Deutsch als Fremdsprache (DaF) students. The data were obtained from the results of observations and questionnaires, and were analyzed using the Miles and Huberman interactive model, namely, data collection, data reduction, descriptive data integration, and drawing conclusions. The results showed that the process of applying this method was well implemented according to the stages in reciprocal teaching. This method affects the way students learn, namely, students try to both independently and collectively understand new material and get consistent reading comprehension. Through this method, students become more enthusiastic, active and motivated to take part in learning German. The reciprocal teaching method is a source of information and an alternative for teachers in determining appropriate and varied learning methods and it can be used as a reference for improving the quality of German learning, particularly at A1 level in high school. The hybrid learning is expected to mediate the students' difficulty in the learning process during the pandemic times. The school should make some innovations that the students update with a technology.